SMS Security Improvement using RSA in Complaints Application on Regional Head Election’s Fraud - Dwi Yuny Sylfania; Fransiskus Panca Juniawan; Laurentinus Laurentinus; Harrizki Arie Pradana (Jurnal Teknologi dan Sistem Komputer, 2019)
In the campaign period of regional heads election, fraud can occur, such as money politics, blaming campaign facilities, campaign time violations, and black campaign. This study implemented a secure SMS application for election fraud complaints as a tool for the society to report all forms of election fraud that have occurred to the election supervisory department safely. The RSA algorithm was applied to encrypt the messages for sender privacy protection. The application was able to perform the message randomization function properly with a 10.44% avalanche effect. Brute force attack using a 16-bit key length needs 3.7 milliseconds for each try to find 32.768 possible private keys.